Hubungan Persepsi Ibu Post Partum Dengan Pemberian Kolostrum Di PMB Mogita Kecamatan Tlanakan Pamekasan - RAHMAWATI, SYLVINA; SUPRAYITNO, EMDAT; PERMATASARI, DIAN (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Colostrum is breast milk given to infants in the first days after childbirth, yellowish color is thicker. Obtained from 69 postpartum mothers only 27 people (40%) who gave colostrum and 42 people (60%) did not giving colostrum to the baby.The purpose of this study is to analyze the relationship of perceptions of postpartum mothers to the provision of colostrum in PMB Mogita Kec. Tlanakan Pamekasan S.ST. This research is an analytic survey with cross sectional approach. The sample used is 43 post partum mothers with sampling technique that is simple random sampling and data collection is done by distributing questioner to respondent. The statistic test used is chi-square. The result showed that almost half of post partum mothers, 19 people (70,37%) had positive perception and gave colostrum. While post partum mother who has negative perception of small part of postpartum mother as much, 10 people (62,5%) and do not give colostrum. Both variables tested through SPSS with Chi-Square statistical test obtained ρ value (0,035) <α (0,05) then Hо rejected and Ha accepted, meaning there is relation of perception of mother of post partum with giving colostrum. Efforts are made of intensive counseling about colostrum through direct communication, education and training conducted by health workers to the village community. .